Epigenetic inactivation of the MIR129-2 in hematological malignancies - Wong, Kwan-Yeung (BioMed Central, 2013)
BACKGROUND: MIR129-2 has been shown to be a tumor suppressor microRNA hypermethylated in epithelial cancers. PATIENTS AND METHODS: Epigenetic inactivation of MIR129-2 was studied by methylation-specific PCR (MSP) in 13 cell lines (eight myeloma and five lymphoma), 15 normal controls and 344 primary samples including acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), chronic lymphocytic leukemia (CLL), non-Hodgkin’s lymphoma (NHL), multiple myeloma (MM) at diagnosis, MM at relapse/progression, and monoclonal gammopathy of undetermined significance (MGUS). Expression of MIR129 and its target, SOX4, in cell lines was measured before and after hypomethylating treatment and MIR129 overexpression. MIR129 expression was correlated with MIR129-2 methylation status in primary lymphoma samples. Tumor suppressor function of MIR129 was demonstrated by MTT and trypan blue exclusion assay after MIR129 overexpression. RESULTS: The sensitivity of the methylated-MSP was one in 10(3). Different MSP statuses, including complete methylation, partial methylation, and complete unmethylation, were verified by quantitative bisulfite pyrosequencing. All five lymphoma and seven of eight myeloma cell lines showed complete and partial MIR129-2 methylation. In primary samples, MIR129-2 methylation was absent in AML and CML, but detected in 5% ALL, 45.9% CLL, 49.5% MM at diagnosis, and 59.1% NHL. In CLL, MIR129-2 methylation adversely impacted on survival (p=0.004). In MM, MIR129-2 methylation increased from 27.5% MGUS to 49.5% MM at diagnosis and 41.5% at relapse/progression (p=0.023). In NHL, MIR129-2 methylation was associated with MIR124-1 and MIR203 methylation (p<0.001), and lower MIR129 expression (p=0.009). Hypomethylation treatment of JEKO-1, homozygously methylated for MIR129-2, led to MIR129-2 demethylation and MIR129 re-expression, with downregulation of SOX4 mRNA. Moreover, MIR129 overexpression in both mantle cell lines, JEKO-1 and GRANTA-519, inhibited cellular proliferation and enhanced cell death, with concomitant SOX4 mRNA downregulation. CONCLUSIONS: MIR129-2 is a tumor suppressive microRNA frequently methylated in lymphoid but not myeloid malignancies, leading to reversible MIR129-2 silencing. In CLL, MIR129-2 methylation was associated with an inferior survival. In MM, MIR129-2 methylation might be acquired during progression from MGUS to symptomatic MM. In NHL, MIR129-2 methylation might collaborate with MIR124-1 and MIR203 methylation in lymphomagenesis.